Deployment of Wi-Fi services for foreign tourists in a mountainous area of Japan - Yasukazu Satake (Netcom)
Foreign travelers access the Internet through their smartphones as a source of travel information during their stay in Japan. However, to date, Wi-Fi spots, which facilitate Internet connectivity, have not been completely deployed in Japan. In this study, we clarify the deployment process of the Wi-Fi spot in Sounkyo area in Kamikawa town, Hokkaido, which is an international tourist site located in a mountainous area. By examining the case of Sounkyo, we reveal that the installation of Wi-Fi spots, which can be used by many people, is influenced by whether or not broadband is being developed in an area. In tourist spots in places where it is difficult to deploy and maintain broadband, implementation of the broadband deployment policy by the national government and local governments is necessary, which is expected to lead to the advancement of international tourism.